Upaya Peningkatan Perilaku Masyarakat melalui Edukasi HIV dan AIDS di Puskesmas Putri Ayu Kota Jambi - Ratu Kusuma (Jurnal Abdimas Kesehatan (JAK), 2023)
HIV/AIDS is one of the endemic diseases in Indonesia, in HIV/AIDS Community, Yayasan Kanti Sehati Sejati Jambi City recorded 1,421 ODHA in  Jambi Province. A total of 1,135 (80%) were in Jambi City (71.63% male). This service activity is carried out at the Puskesmas Putri Ay  Jambi City, where cases of HIV/AIDS always increase every year. In 2021 there were 70 HIV/AIDS cases (2 people died due to complications of pulmonary tuberculosis). This figure is higher than in previous years, 2018 (27 cases), 2019 (40 cases), 2020 (52 cases). Based on problem identification, there are 2 partner problems, namely program problems and community problems. The purpose of the education implementation is to increase the knowledge and attitudes of participants after attending education about HIV/AIDS. Educational activities are carried out in the form of group education, in 1 meeting for ± 60 minutes in the hall Puskesmas Putri Ayu. Before delivering the material, leaflets were distributed to each participant. Furthermore, the material was delivered through power point using lecture, discussion, question and answer methods and sharing experiences. Before and after education, pretest and posttest were carried out. The results obtained were that there were 11 participants who attended the education and 1 of them was ODHA; teenagers, most of the women who work as housewives without income with the most education are elementary school. There was an increase in the average knowledge of 1.5 and an increase in the average attitude of 2.1. Through this activity, it is hoped that the behavior of the community will improve so that the number of people living with HI/AIDS (ODHA) is reduced